(untitled) (Bangladesh Journal of Microbiology, 2018)
Current study attempted to examine the chances of microbial contamination within the common flavored milk products consumed by the locality of Dhaka city, Bangladesh. All samples, collected from different super shops, revealed the presence of total viable bacterial counts within the range of 2.5×104 to 8×105 cfu/ mL. Staphylococcus spp., Pseudomonas spp., and coliforms were noticed to be predominant and were recovered from 6 out of 10 samples with an average load of 103-105 cfu/mL. Salmonella spp. was also detected in one sample. Study of the antibiotic susceptibility test further demonstrated that all the bacterial isolates were resistant against most of the commonly used antibiotics with the multi- drug resistant traits in several cases. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 11-15